Composition and Biochemical Methane Potential from Different Typha Components - Sale, N. A.; Kohn, R. A.; Sale, A.; Mohammed, U. S.; Dalha, I. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Invasive species are recognized as one of the main causes of erosion of global biodiversity which represent one of the major environmental challenges of the 21st century. Typha is among the fifth most invasive species in West Africa, Nigeria included. Presently in Hadejia Valley Wetlands of Nigeria, typha grass has been perceived as a threat to the surrounding communities. Although some research efforts have shown it can be used as a resource material for renewable energy or animal feed, its use has not yet become a commercial practice. This study investigates compositional characteristic using in vitro digestibility and biogas production from different Typha botanical fractions using anaerobic digestion inoculated with rumen microorganisms. Treatments considered were single plant components as well as combinations. The results show that spike (seed) had the highest soluble crude protein and the leaves had the highest energy content (cellulose and hemicellulose). The leaf and stem at full maturity had a lignin content of 18-20%. Rhizome and stem contained higher ash content while root had greater total volatile solid. The spike yielded the most biogas (457 ml/g) at 60 days retention period. The root component yielded the least gas (259 ml/g) over the same period. The seed pod produced the most methane gas per weight of VS (255 ml/gVS). Blending leaf and stem or root and rhizome increased the volume of biogas generated (399 ml/g and 442 ml/g respectively) while a combination of all components of the plant decreased the volume of gas (388 ml/g – 289 ml/g). The combination of the root and the rhizome produced a higher volume of methane (254 ml/g) than either component by itself (root with 160 ml/g while rhizome 226 ml/g). Different typha components has different compositional characteristic which influence the activity of anaerobic microorganism and affect the volume and quality of biogas produced. Rumen microorganisms digest typha component and spike gives the highest gas volume per grams of typha biomass while rood produce the least volume. Combination of different typha component affect the volume of gas generation defending of which component of plants were mixed.